1997
DOI: 10.1126/science.276.5317.1408
|View full text |Cite
|
Sign up to set email alerts
|

Severe Fibronectin-Deposit Renal Glomerular Disease in Mice Lacking Uteroglobin

Abstract: Despite myriads of biological activities ascribed to uteroglobin (UG), a steroid-inducible secreted protein, its physiological functions are unknown. Mice in which the uteroglobin gene was disrupted had severe renal disease that was associated with massive glomerular deposition of predominantly multimeric fibronectin (Fn). The molecular mechanism that normally prevents Fn deposition appears to involve high-affinity binding of UG with Fn to form Fn-UG heteromers that counteract Fn self-aggregation, which is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
156
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(169 citation statements)
references
References 39 publications
(7 reference statements)
10
156
2
1
Order By: Relevance
“…The proband's father died of cancer at 30 years of age. A heterozygous 2918AϾG mutation causing a Y973C change in repeat III 4 was found in the index case and in her affected daughter but not in the unaffected father ( Fig. 1 b and c and SI Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proband's father died of cancer at 30 years of age. A heterozygous 2918AϾG mutation causing a Y973C change in repeat III 4 was found in the index case and in her affected daughter but not in the unaffected father ( Fig. 1 b and c and SI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the genetic abnormality underlying GFND was still unknown (3)(4)(5). By whole-genome linkage analysis in a large pedigree, a gene locus for GFND was mapped on 1q32, within a 4.1-cM interval that contains a cluster of genes involved in the regulation of complement activation (RCA) (6).…”
mentioning
confidence: 99%
“…It should be noted, however, that UG knockout mice have elevated plasma sPLA 2 activities [46]. The UG-deficient mice also manifest several phenotypes [46][47][48][49], suggesting a multifunctional nature of this protein. UG is present in alveolar and bronchial secretions and most likely protects the phospholipid component of lung surfactant by inhibiting the lung-specific sPLA 2 activity [50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we (18) and others (19) have previously demonstrated that overexpression of UG in cancer cells reverses their transformed phenotype and neoplastic potential. We also demonstrated that UG-knock-out (UG-KO) mice (16) are highly susceptible to lung tumorigenesis by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone, a carcinogen in cigarette smoke (20). Previously, we reported that the UG gene is constitutively expressed at a high level in the lung epithelia (21).…”
mentioning
confidence: 99%
“…It is constitutively expressed in the lungs of all mammals, and targeted disruption of the UG gene in mice (16) increases susceptibility to pulmonary inflammation (17). Moreover, we (18) and others (19) have previously demonstrated that overexpression of UG in cancer cells reverses their transformed phenotype and neoplastic potential.…”
mentioning
confidence: 99%